Molecular mechanisms of lncRNA SMARCC2/miR-551b-3p/TMPRSS4 axis in gastric cancer. (1st April 2018) - Yuan, Hao; Chen, Zhaofeng; Bai, Suyang; Wei, Hui; Wang, Yuping; Ji, Rui; Guo, Qinghong; Li, Qiang; Ye, Yuwei; Wu, Jing; Zhou, Yongning; Qiao, Liang
Abstract: Decreased expression of miR-551b-3p has been identified in gastric cancer tissues but its biological role and underlying mechanism in this malignancy is poorly understood. In this study, we show that the expression of miR-551b-3p negatively correlates with the depth of tumour invasion and lymphatic metastasis, but it positively correlates with tumour differentiation and the patient survival. MiR-551b-3p negatively affects the proliferation, mobility and invasiveness of gastric cancer cells. LncRNA SMARCC2 inhibits the expression of miR-551b-3p through binding to its mRNA response elements in gastric cancer cells. Overexpression of LncRNA SMARCC2 enhances the proliferation and migration of gastric cancer cells, while inhibition of LncRNA SMARCC2 does the opposite. TMPRSS4 is a direct target gene of miR-551b-3p. We conclude that miR-551b-3p functions as a tumour suppressor gene in gastric cancer, and its function is regulated by LncRNA SMARCC2/miR-551b-3p/TMPRSS4 axis.